Constructing Gender Through Popular Culture : Semiotic Perspective - Jong Li Fa; Aritonang, Angelin; Lusi Stasia; M. Imam mahdilawa; Syafira Rizki Putri; Afifulloh, M (English Journal Antartika, 2023)
Gender is a complex issue because it is a social identity that is dynamic in nature. It exists according to the culture to which a society belongs and is not fixed. Films, as a popular medium, often convey messages about gender issues and are implicit in their nature. This research explores the construction of gender in Original Netflix's Purple Heart. This research is qualitative descriptive research with the semiotic approach of Rolland Barthes. The result of the study showed that the film shows how gender is constructed through the intense relationship between men and women. Furthermore, the film Purple Hearts constructs gender identity unequally, in particular regarding the roles of men and women and the treatment of women.